MyCourseMap: an interactive visual map to increase curriculum transparency for university students and staff - Tee, Lisa; Hattingh, L.; Rodgers, Katherine; Ferns, Sonia; Chang, Vanessa; Fyfe, Sue (2015)
MyCourseMap is an interactive curriculum map created to increase curriculum transparency for both students and staff. It provides access to the entire curriculum at a glance, displays alignment of unit learning outcomes, assessments, course learning outcomes, and graduate attributes and links video from employers, graduates and students to help students reflect on the curriculum and its relevance. A prototype developed for the Bachelor of Pharmacy course at Curtin University as a proof-of-concept was tested and evaluated in 2014 and 2015. This evaluation utilised a mixed-methods approach using a blend of quantitative and qualitative data through online survey and structured focus group discussions. From the evaluation, the perceived benefits of the MyCourseMap include students’ increased understanding of their degree structure and its relevance to their chosen profession. From a staff perspective, the MyCourseMap helps with review and development of curriculum and professional accreditation. Barriers and challenges have led to prototype refinements.